Basic characteristics of ground vibration sensors for the detection of debris flow - Itakura, Y.; Fujii, N.; Sawada, T. (Physics and chemistry of the earth. Part B, Hydrology, oceans and atmosphere, 2000)
An acoustic sensor has been designed and built to sense ground vibration with a microphone installed underground inside a steel pipe. The sensor has detected debris flows in torrents in Japan. Other sensors have been used to sense ground vibrations similarly and they also have been tested in the field individually. Basic characteristics of three different ground vibration sensors, an acoustic, a piezoelectric, and a moving-coil sensor are compared in the same test field. Two of them, a microphone sensor and a piezoelectric sensor, have higher signal-to-noise ratios (S/N ratios) than the moving-coil sensor. The microphone sensor has the maximum S/N ratio at our experimental field and is the most useful one.